Computational investigation of the conformational dynamics in Tom20‐mitochondrial presequence tethered complexes. Issue 1 (16th November 2018) - Srivastava, Arpita; Tama, Florence; Kohda, Daisuke; Miyashita, Osamu
Abstract: The translocase of the outer membrane (TOM) mediates the membrane permeation of mitochondrial matrix proteins. Tom20 is a subunit of the TOM complex and binds to the N‐terminal region (ie, presequence) in mitochondrial matrix precursor proteins. Previous experimental studies indicated that the presequence recognition by Tom20 was achieved in a dynamic‐equilibrium among multiple bound states of the α‐helical presequence. Accordingly, the co‐crystallization of Tom20 and a presequence peptide required a disulfide‐bond cross‐linking. A 3‐residue spacer sequence (XAG) was inserted between the presequence and the anchoring Cys residue at the C‐terminus to not disturb the movement of the presequence peptide in the binding site of Tom20. Two crystalline forms were obtained according to Ala or Tyr at the X position of the spacer sequence, which may reflect the dynamic‐equilibrium of the presequence. Here, we have performed replica‐exchange molecular dynamics (REMD) simulations to study the effect of disulfide‐bond linker and single amino acid difference in the spacer region of the linker on the conformational dynamics of Tom20‐presequence complex. Free energy and network analyses of the REMD simulations were compared against previous simulations of non‐tethered system. We concluded that the disulfide‐bond tethering did not strongly affect the conformational ensemble of the presequence peptide in the complex. Further investigation showed that the choice of Ala or Tyr at the X position did not affect the most distributions of the conformational ensemble of the presequence. The present study provides a rational basis for the disulfide‐bond tethering to study the dynamics of weakly binding complexes.